Scalar field cosmology II : superfluidity, quantum turbulence, and inflation - Huang, Kerson. (2013)
We generalize the big bang model in a previous paper by extending the real vacuum scalar field to a complex vacuum scalar field, within the FLRW framework. The phase dynamics of the scalar field, which makes the universe a superfluid, is described in terms of a density of quantized vortex lines, and a tangle of vortex lines gives rise to quantum turbulence. We propose that all the matter in the universe was created in the turbulence, through reconnection of vortex lines, a process necessary for the maintenance of the vortex tangle. The vortex tangle grows and decays, and its lifetime is the era of inflation. These ideas are implemented in a set of closed cosmological equations that describe the cosmic expansion driven by the scalar field on the one hand, and the vortex–matter dynamics on the other. We show how these two aspects decouple from each other, due to a vast difference in energy scales. The model is not valid beyond the inflation era, but the universe remains a superfluid afterwards. This gives rise to observable effects in the present universe, including dark matter, galactic voids, nonthermal filaments, and cosmic jets.